Three levels of root insertion in Basque intransitive verbs - Ane Berro (Journal of Portuguese Linguistics, 2012)
Intransitive verbs in Basque vary depending on their subject case and auxiliary selection: (i) some of them (considered unaccusatives and inchoatives) always have an absolutive subject and an intransitive auxiliary; (ii) others (prototypical unergatives) show diachronic and dialectal variation (absolutive subject and intransitive auxiliary vs. ergative subject and transitive auxiliary); and (iii) other unergative verbs with which an ergative subject and a transitive auxiliary prevail cross-dialectally. We propose a sublexical structure (Ramchand 2004, 2008) where verbs can be decomposed in three subevents. Unaccusative verbs in Basque are Path predicates, selecting a V of process (VPROCP) that, in the case of telic verbs, takes an adpositional phrase (PP) as complement. Atelic unaccusative verbs and unergative verbs having intransitive morphology are similarly Path predicates, but instead of a result PP, they can select a Rheme of process. In unergative verbs with transitive morphology no V of process is projected, but a little v of initiation (vINIT or vDO). Verbal roots may be inserted at three levels in Basque: vP, VP or PP. The last two are below an AspectualP involved in absolutive case assignment and intransitive auxiliary selection. Thus, depending on where the root is inserted has an effect on the alignment.